Template for evaluating dexterity in non-surgical periodontal, prophylactic, and cosmetic clinical instrumentation - Adamu, V. E.; Eneojo, Ndidiamaka Ijeoma (Orapuh Protocols, 2023)
The assessment of non-surgical periodontal, prophylactic, and cosmetic instrumentation in the clinic requires an objective evaluation machinery to elicit the right feedback. We have developed this clinical assessment template with the hope that dental clinical training instructors would adopt it to give their students fair and equitable feedback to non-surgical periodontal, prophylactic, and cosmetic instrumentation.